2022
DOI: 10.1038/s41598-022-19752-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient biodegradation of di-(2-ethylhexyl) phthalate by a novel strain Nocardia asteroides LMB-7 isolated from electronic waste soil

Abstract: The di-2-ethylhexyl phthalate (DEHP) degrading strain LMB-7 was isolated from electronic waste soil. According to its biophysical/biochemical characteristics and 16S rRNA gene analysis, the strain was identified as Nocardia asteroides. Optimal pH and temperature for DEHP degradation were 8.0 and 30 °C, respectively, and DEHP removal reached 97.11% after cultivation for 24 h at an initial concentration of 400 mg/L. As degradation intermediates, di-butyl phthalates, mono-2-ethylhexyl phthalate and 2-ethylhexanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Therefore, the increase in the temperature in surface water may be another possible reason for its high occurrence in the influent of WTPs in the summer period. In contrast, several studies with similar climatic seasons to this study also claimed that higher phthalate levels were observed in the dry season of winter compared to the wet season of summer. , For another reason, previous studies explained that biodegradation plays one of the major roles in the degradation of phthalates in surface water. , Thus, another strong possibility could be the lower activity levels of microbial communities in the winter season, resulting in less phthalate degradation and contributing to its high concentration in winter compared to the summer season …”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Therefore, the increase in the temperature in surface water may be another possible reason for its high occurrence in the influent of WTPs in the summer period. In contrast, several studies with similar climatic seasons to this study also claimed that higher phthalate levels were observed in the dry season of winter compared to the wet season of summer. , For another reason, previous studies explained that biodegradation plays one of the major roles in the degradation of phthalates in surface water. , Thus, another strong possibility could be the lower activity levels of microbial communities in the winter season, resulting in less phthalate degradation and contributing to its high concentration in winter compared to the summer season …”
Section: Resultscontrasting
confidence: 63%
“…33,34 For another reason, previous studies explained that biodegradation plays one of the major roles in the degradation of phthalates in surface water. 53,54 Thus, another strong possibility could be the lower activity levels of microbial communities in the winter season, resulting in less phthalate degradation and contributing to its high concentration in winter compared to the summer season. 33 Due to the limited number of samples, we could not find any statistical differences (p > 0.05) on the impact of location and seasonal variations of DEHP in influent (S1) of 6 WTPs, we observed that the highest DEHP concentrations in the S10.…”
Section: Extraction and Gc−ms Analysismentioning
confidence: 99%